THE MONOGRAPH “TUBERCULOSIS. EPIDEMIOLOGY AND DISEASE PREVENTION AND CONTROL IN CONTEMPORARY SETTINGS OF THE HIGH NORTH (THE CASE OF SAKHA REPUBLIC (YAKUTIA))” - Ekaterina Sergeevna Pavlova (V mire nauchnykh otkrytiy, 2016)
We present a review of the monograph written by a group of authors and edited by Professor Savilov E.D., Honored Science Worker of the Russian Federation. The monograph is the first presenting consolidated data from collaborative work between the Research-and-Practice Center for Tuberculosis of the Sakha Republic (Yakutia) and Irkutsk Scientific Center for Problems of Family Health and Human Reproduction, shedding light on the aspects of tuberculosis control and prevention in Yakutia, a region with low population density, on the molecular genetic characteristics of M. tuberculosis circulating in the region, and its drug resistance profile. The monograph is intended to all professionals engaged in tuberculosis control.